Proactive Response Inhibition and Subcortical Gray Matter Integrity in Traumatic Brain Injury. (March 2017) - Hermans, Lize; Beeckmans, Kurt; Michiels, Karla; Lafosse, Christophe; Sunaert, Stefan; Coxon, James P.; Swinnen, Stephan P.; Leunissen, Inge
Background . Traumatic brain injury (TBI) has been associated with impairments in inhibiting prepotent motor responses triggered by infrequent external signals (ie, reactive inhibition). It is unclear whether proactive preparation to inhibit upcoming responses is also affected (ie, proactive inhibition). Successful inhibition relies on frontosubcortical interactions; therefore, impairments might be linked with gray matter atrophy in subcortical structures. Objective . We investigated reactive and proactive inhibition in TBI and control groups, and their relationship with subcortical gray matter. Methods . Participants performed a response inhibition task in which the probability of stopping was manipulated. Reactive inhibition was measured as the stop-signal reaction time (SSRT) when the probability of stopping was low. Proactive inhibition was measured as the change in SSRT and in go response time with increasing probability of stopping. Subcortical gray matter structures were automatically segmented with FSL-FIRST. Group differences in subregional volume and associations with reactive and proactive inhibition efficiency were investigated using shape analysis. Results . Reactive inhibition was impaired in TBI, as indicated by longer SSRTs. Moreover, the degree of atrophy in subregions of subcortical structures was predictive for SSRT in TBI. In contrast, proactive inhibition was not affected because both groups showed no response time slowing as a function of stopping probability. Proactive inhibition efficiency could be predicted by local volume in the anterior left putamen, bilateral pallidum, and right thalamus in controls but not in TBI. Conclusions . Our results reveal that proactive inhibition seems unaffected in TBI and that volume of subregions of subcortical nuclei is predictive for response inhibition proficiency and of clinical relevance in TBI.